A Quantum Secret Sharing Scheme Using Orbital Angular Momentum onto Multiple Spin States Based on Fibonacci Compression Encoding*Supported by the National Natural Science Foundation of China under No. 61702427 and the Doctoral Program of Higher Education under Grant No. SWU115091, the Fundamental Research Funds for the Central Universities (XDJK2018C048), and the financial support in part by the 1000-Plan of Chongqing by Southwest University under No. SWU116007, the National Natural Science Foundation of China under Grant No. 61772437, and Sichuan Youth Science and Technique Foundation under No. 2017JQ0048, the National Natural Science Foundation of China under Grant No. 61401371, Josef Pieprzyk has been supported by National Science Centre, Poland, Project Registration Number UMO-2014/15/B/ST6/05130. (October 2018) - Lai 赖, Hong 红; Luo 罗, Ming-Xing 明星; Xu 徐, Yong-Jian 永健; Pieprzyk, Josef; Zhang 张, Jun 军; Pan 潘, Lei 磊; Orgun, Mehmet A.
Abstract: Since the use of a quantum channel is very expensive for transmitting large messages, it is vital to develop an effective quantum compression encoding scheme that is easy to implement. Given that, with the single-photon spin-orbit entanglement, we propose a quantum secret sharing scheme using orbital angular momentum onto multiple spin states based on Fibonacci compression encoding. In our proposed scheme, we can represent the frequency of any secret message which is typically collection of bits encodings of text or integers as a bitstring using the base Fibonacci sequence, which is encoded multiple spin states for secret shares transmitted to participants. We demonstrate that Fibonacci compression encoding carries excellent properties that enable us to achieve more robust quantum secret sharing schemes with fewer number of photons.